Asian Educators Experiencing the Bamboo Ceiling: A Canadian Case Study of Systemic Barriers in Hiring, Advancement, and Promotion - Reid, Mary; Reid, Steven; Eizadirad, Ardavan (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2024)
Our study amplifies the voices of Asian educators undergoing career advancement in a large district school board with a significant Asian student population in Ontario, Canada. Our data sources included survey results from 234 Asian educators and focus group transcriptions from 83 Asian educators. Grounded in Asian critical race theory (“AsianCrit”), our findings show that Asian educators faced the “bamboo ceiling,” wherein institutional barriers and inequities in relation to their Asian identity limited their career advancement when applying for leadership roles. Through a thematic analysis, we found systemic barriers: (a) pressure to conform to whiteness to advance their careers, (b) accent and name discrimination, and (c) colonial ideologies that have been normalized and embedded in leadership selection processes. Our research addresses significant gaps in the literature on Asian Canadian educators’ experiences in career advancement and contributes to the important development of AsianCrit theory.